Jus kombinasi semangka kuning (Citrullus lanatus (Thunb.) Matsum. & Nakai) - pisang raja (Musa acuminata x Musa balbisiana) meningkatkan endurance dalam aktifitas aerobik - Farida Farida; Afina Rachma Sulistyaning; Hesti Permata Sari (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Plantains are high in potassium and glucose, while yellow watermelons are high in citrulline, antioxidants and fluids. The combination juice of plantain and yellow watermelon provides glucose and fluids, suppresses lactic acid and muscle inflammation, so will improve endurance during aerobic exercise. The aim of this study was to determine the effect of combining juices of yellow watermelon plantains on aerobic swimming endurance in Sprague-Dawley rats. The design of this study was true experimental and used a post-test only with a controlled group. The 21 male Sprague Dawley rats, were divided into three groups, the control (K), which were given one dose of juice (P1) and two doses (P2). Rats were observed for the length of swimming. One-Way Anova and Post-Hoc LSD were used to analyze the data. The results of this study found that on average P2 with a double dose of juice had a longer swim. The P1 swim 390,57 seconds longer than control, while P2 swim 757,57 seconds longer than control, while P2 could swim 367 seconds longer than P1. There was a difference in swim length (p < 0,001) in each group after intervention with variation doses. The conclusion was that there was a difference in endurance in each group after receiving a combined juice with variation doses.